Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton classic editions, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (Grands classiques de l'érotologie moderne, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Feminist contentions: A philosophical exchange - Benhabib, Seyla; Butler, Judith; Cornell, Drucilla; Fraser, Nancy (Thinking gender, 1995)
Ce volume présente un débat entre quatre des plus grandes théoriciennes féministes des États-Unis. Seyla Benhabib, Judith Butler, Drucilla Cornell et Nancy Fraser discutent de certaines des questions clés auxquelles la théorie féministe est confrontée. Chacune articule sa propre position dans un essai initial, puis répond aux autres dans un essai de suivi, rendant possible une conversation entre ces penseuses féministes influentes. Commencé comme un symposium sur la question du féminisme et du postmodernisme, le volume s'est transformé en une discussion sur des questions plus larges telles que l'utilité du postmodernisme en tant que concept théorique; le rôle de la philosophie dans la critique sociale ; comment le récit historique est le mieux conceptualisé ; le statut du sujet du féminisme ; et les effets politiques des différentes formulations de toutes ces questions.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; postmodernisme; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis